2019
DOI: 10.21608/asejaiqjsae.2019.26436
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Milk Thistle (Silybum Marianum L) Seeds on Carbon Tetrachloride - Induced Hepatotoxicity in Rats

Abstract: The current research aimed to investigate the therapeutic effect of milk thistle (Silybum marianum L) seeds (MTS) powder compared with hepaticum drug on carbon-tetrachloride (CCl4) caused hepatotoxicity in rats. Thirty six female albino rats weighting 140±20g were divided into 6 groups. The 1 st group was fed on basal diet as the negative control group (G1), while the other five groups were injected by CCl4 (i.p). The 2 nd group was the positive control group (G2). Groups from 3 rd to 5 th were fed on basal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…This indicate that the negative effect of oils on the HDL-cholesterol level is strain-related and specific for obese Zucker rats. Nevertheless, our results are in accordance with the study by Zaki et al 53 who observed that a dietary supplementation with only 1% milk thistle seeds can reduce plasma cholesterol concentration in rats with carbon tetrachloride-induced hepatotoxicity, whereas 3% supplementation can normalize the cholesterol to a level found in healthy rats. Our study also shows that the cholesterol-lowering effect of milk thistle seeds is associated with their lipid fraction of which PUFAs are its most important part.…”
Section: Discussionsupporting
confidence: 93%
“…This indicate that the negative effect of oils on the HDL-cholesterol level is strain-related and specific for obese Zucker rats. Nevertheless, our results are in accordance with the study by Zaki et al 53 who observed that a dietary supplementation with only 1% milk thistle seeds can reduce plasma cholesterol concentration in rats with carbon tetrachloride-induced hepatotoxicity, whereas 3% supplementation can normalize the cholesterol to a level found in healthy rats. Our study also shows that the cholesterol-lowering effect of milk thistle seeds is associated with their lipid fraction of which PUFAs are its most important part.…”
Section: Discussionsupporting
confidence: 93%
“…Silymarin was used in this study as a reference herbal drug for its well-identified hepatoprotective mechanism. The hepatoprotective actions of silymarin have been previously imputed to its antioxidant properties [56, 57,58,59]. It was reported that silymarin inhibits liver injury by maintaining the integrity of the plasma membrane, inhibits the secretion of liver enzymes in blood, and suppresses apoptosis in the hepatocytes [60].…”
Section: Liver Function Biomarkers In Experimental Groups Intoxicated By CCLmentioning
confidence: 99%